Practice of a new model in the management of endoscopic surgical instruments base on integration management of Operating Room and Central Sterile Supply Department (手供一体化下腔镜手术器械的新型管理模式实践) - YUE Yuan (岳圆); FU Yang (付扬) (Journal of International Translational Medicine Limited, 2021)
This paper summarized the practice of a new model in the management of endoscopic surgical instruments base on integration management of Operating Room and Central Sterile Supply Department. Surgery-related resources can be re-optimized by the establishment of a branch of Central Sterile Supply Department in the Operating Room, and integration management of Operating Room and Central Sterile Supply Department can be achieved, showing a positive effect in improving surgical effectiveness and reduce the risk of nosocomial infection. (本文总结了手术室与消毒供应中心一体化(手供一体化)下腔镜手术器械的消毒供应管理经验。手术室设立消毒供应中心分部, 是对手术现有资源的再优化, 有助于实现器械消毒供应与手术周转的统一管理, 对提高手术时效性、降低院内感染等具有积极意义。)